Midtemperature solar systems test facility predictions for thermal performance based on test data: AAI solar collector with pressure-formed glass reflector surface - Harrison, T.D. (Sandia National Laboratories, 1981)
Sandia National Laboratories, Albuquerque (SNLA), is currently conducting a program to predict the performance and measure the characteristics of commercially available solar collectors that have the potential for use in industrial process heat and enhance oil recovery applications. The thermal performance predictions for the AAI solar line-focusing slat-type collector for five cities in the US are presented. (WHK)